Integrating Transport as A Human Right: Addressing Accessibility and Equity in Public Transportation Systems - Isatou Jallow; I Nyoman Aji Duranegara Payuse; I Made Suwitra; I Ketut Sukadana (Fakultas Hukum, Universitas Warmadewa, 2025)
The recognition of transport as a fundamental human right has gained increasing attention in policy and academic discourse. Access to reliable and equitable public transportation is crucial for promoting social inclusion, economic opportunity, and sustainable development. However, many urban centers, particularly in developing countries, face significant challenges related to accessibility and equity in public transport systems. This research examines the legal and policy frameworks supporting transport as a human right and explores global best practices in achieving accessible public transport. Using a normative juridical method, this study analyzes international human rights treaties, national regulations, and urban transport policies. Comparative case studies of cities such as Bogotá, Curitiba, and Jakarta provide insights into the successes and challenges in integrating transport as a human right. Findings indicate that robust public transport infrastructure, political commitment, community participation, and integration with land-use planning are essential for ensuring accessibility and equity. However, barriers such as inadequate funding and policy fragmentation continue to hinder progress in many regions. The study concludes that recognizing transport as a human right requires legal and institutional reforms that prioritize marginalized communities, enhance investment in inclusive infrastructure, and foster participatory urban planning. Lessons from successful cities offer a roadmap for policymakers to develop equitable and sustainable transport systems that uphold human rights and social justice.